Viability of black currant pollen before and after cryopreservation in liquid nitrogen, and its morphological features - O. A. Tikhonova; O. A. Gavrilova; E. A. Radchenko; V. G. Verzhuk; A. V. Pavlov (Труды по прикладной ботанике, генетике и селекции)
Background. Learning about morphological and biological features of pollen is very important to make correct estimations of plant productivity and breeding efficiency.Materials and methods. The viability of black currant pollen was analyzed in 2019 at the Laboratory for Long-Term Storage of Plant Genetic Resources, N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR). Eleven black currant cultivars of various ecogeographic and genetic origin maintained at Pushkin and Pavlovsk Laboratories of VIR served as the material for the research. Pollen viability was tested on an artificial medium with 10% sucrose and 0.8% agar. Morphological studies were carried out using light and confocal laser scanning microscopy at the Palynology Laboratory and the Core Centrum of Cell and Molecular Technologies in Plant Science housed by the Komarov Botanical Institute (BIN).Results and conclusion. The prevailing adverse weather conditions in 2019 produced a negative impact on the process of male generative structure formation. The level of pollen viability, depending on the cultivar, ranged from 17.98 to 58.60%. After exposure to liquid nitrogen (–196°C) for 6 months, the number of germinated pollen grains increased 1.1 to 3.2 times in all the studied cultivars, except one (‘Pozdnyaya poslevoennaya’, k-7652). A palynomorphological study revealed that reduced pollen viability in some cultivars (‘Krasnoyarskaya 1018’, k-7607; ‘Tsema’, k-25900; ‘Pozdnyaya poslevoennaya’, k-7652) was associated with morphological deviations in the sporoderm structure (small pollen grains, exine thickening and formation of verrucate mesoporium surfaces). A low positive correlation was observed between the level of pollen viability and the diameters of the pore (r = 0.43) and pollen grain (r = 0.27). An insignificant negative correlation was apparent between the level of viability and the exine thickness (r = –0.33).